SURGICAL RESECTION VERSUS ABLATION FOR EARLY-STAGE HEPATOCELLULAR CARCINOMA: A RETROSPECTIVE COHORT ANALYSIS - Lee, Grace C. (Am J Surg, 2019)
BACKGROUND: The most appropriate treatment for early-stage hepatocellular carcinoma (HCC) remains unclear. This study compared the association of resection versus ablation with overall survival (OS) in patients with early-stage HCC. METHODS: Using the National Cancer Database (NCDB), patients diagnosed with stage I/II HCC between 2004–2014 were identified. Cox analysis was used to determine predictors of OS. RESULTS: We identified 53,161 patients, of whom 15.9% underwent ablation and 14.5% underwent resection. Patients with fewer comorbidities, larger tumors, and private insurance were more likely to undergo resection. Resection was associated with significantly improved OS compared to ablation (HR 0.58, 95% CI 0.54–0.61, p<0.001), at all tumor sizes (p<0.05) and any degree of liver fibrosis (p<0.05). CONCLUSIONS: Resection of HCC tumors of all sizes and any degree of underlying fibrosis was associated with significantly improved OS compared with ablation. There was pronounced variability in the use of ablation versus resection for early-stage HCC.